Presence and antimicrobial resistance of ESBL Escherichia coli from fecal samples of dairy cattle in northern Ecuador - Calvopiña Montenegro, Pamela Carolina (2024)
Escherichia coli causes colibacillosis in farm animals that act as reservoirs for pathogenic strains. Antimicrobial resistance of E. coli producing Extended Spectrum Beta-lactamases [ESBL] is a serious public health problem that can be attributed to factors related to food consumption and contact with domestic animals. This study aimed to determine the presence and patterns of antimicrobial resistance of ESBL E. coli isolated from fecal samples from dairy cattle in the Pichincha province. A total of 182 bovine feces samples were analyzed, 112 samples from cattle slaughtered at the official slaughterhouse in Quito-Pichincha province, and 70 samples from the collection of the Foodborne Diseases and Antimicrobial Resistance Research Unit [UNIETAR]. The isolation of ESBL E. coli, biochemical identification, and resistance tests using the main antibiotics were carried out at UNIETAR. It was possible to identify 93 positive samples for ESBL E. coli (51%), phenotypic analysis revealed that antibiotics such as amoxicillin plus clavulanic acid, cefepime, ceftazidime, ciprofloxacin, amikacin, tetracycline, presented resistance higher than 80%. Furthermore, low resistance to nitrofurantoin, cefoxitin, and ertapenem was observed, while no isolate was resistant to tigecycline. One hundred percent of the isolates presented multi-resistance phenotypes, with the most frequent pattern being composed of 7 families of antibiotics. In conclusion, these results suggest that E. coli from dairy cattle origin could be an important reservoir of ESBL genes.